THE ROLE OF MATTOANGING FARMER GROUP IN INCREASING MAIZE (Zea mays) PRODUCTION IN MASSEPE VILLAGE - Upri, Ali; Padapi, Astrini; R, Fitriani (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
This study aims to determine the role of the Mattoanging farmer group in increasing maize production in the Massepe Village. This quantitative descriptive research uses a non-experimental approach with a survey type. The research using a questionnaire obtained an average percentage in learning classes 72.3%, in collaboration vehicles of 75.8%, and production units of 81.2%. After being analyzed using the Rank-Spearman Correlation, the correlation coefficient in the learning class was 0.678. In cooperative vehicles, it is 0.683; in production units, it is 0.654. These three values indicate a strong relationship with a positive direction. The significance value obtained from the three variables is below 0.05 (Î± = 5%). This means that H0 is rejected and H1 is accepted, which means that there is a significant relationship between the role of the Mattoanging farmer group as a learning class, a vehicle for cooperation, and a production unit in increasing maize production in Massepe Village, Tellu Limpoe District, Sidenreng Rappang Regency.